Age-Associated with Worsening of Neurological Deficits in Ischemic Stroke Patients in Abdoel Wahab Sjahranie Regional Hospital, Samarinda - Indria, Muhamad Dino; Rachmi, Eva; Hutahaean, Yetty Octavia (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2024)
Highlights: The worsening of neurological deficits in ischemic stroke patients is associated with the patient's age, with those over 45 years old having a higher risk. The worsening of neurological deficits in ischemic stroke patients does not correlate with hemoglobin level, hematocrit value, gender, smoking history, blood pressure, or hyperglycemic state.   Abstract Introduction: Treatment of impairment is an important step to prevent advanced neurological deficits in ischemic stroke medicine. Ischemic stroke patients with likely worsening neurological deficits should receive appropriate interventions. Therefore, this study aimed to examine predictors that can identify worsening neurological deficits. Methods: This study used a cross-sectional design on 74 hospitalized ischemic stroke patients at Abdoel Wahab Sjahranie Regional Hospital, Samarinda, in 2019. The worsening of neurological deficits was based on the progression of the National Institutes of Health Stroke Scale (NIHSS) scores at hospital admission and discharge. Age, hemoglobin level, hematocrit value, gender, smoking history, blood pressure, and hyperglycemic state were based on patient data at the beginning of hospital admission. The Chi-Square and Fisher's exact tests were used in bivariate analysis. Results: The results showed that age had a significant association with the worsening of neurological deficits in ischemic stroke patients (p = 0.024). Hemoglobin level, hematocrit value, gender, smoking history, blood pressure, and hyperglycemic state showed no relationship with worsening neurological deficits in ischemic stroke patients (p > 0.05). Conclusion: Age can serve as a predictor of worsening neurological deficits in ischemic stroke patients, with those aged over 45 years old having a higher risk. Meanwhile, the other factors were not associated with a worsening neurological deficit in ischemic stroke patients.